Temporomandibular pain and jaw movement: The hybrid model - Talal H Salame (Wolters Kluwer Medknow Publications, 2016)
Introduction: TMD sufferers are not able to move their jaw normally. Several theories tried to demonstrate the relation between pain and movement in patients with TMD. The Vicious Cycle Theory (VCT) suggested that a sore muscle caused by prolonged contraction would lead to more muscle activity which would lead to more pain and a continuation of the vicious cycle. The Pain Adaptation Model (PAM) suggested that a decreased activity of a sore muscle responsible for producing movement is more likely in order to reduce speed and the detrimental effect of movement and promote healing. The hypothesis: The Hybrid model, developed in 2006, suggested that both the VCT and the PAM are valid and applicable in orofacial pain patients, depends on the origin of the pain whether from the muscle or from the joint. Evaluation of the hypothesis: The data from a study on pain and movement showed that both increased and decreased activities of masticatory muscles are possible in the presence of pain as the system reacts differently if the pain originates from the muscle or from the joint. In case of muscle pain, the data showed decreased activity of agonistic muscles during movement and this is conformed to the PAM. When the pain is in the joint, both decreased and increased activities were observed throughout the movement. Neurophysiological mechanisms that govern the relationship between pain and movement, as well as clinical manifestation of the pain, are different if the pain arises from the muscle or from the joint. Finding new treatment approaches that deal with the muscle pain and joint pain as two different entities seems to be of utter importance in orofacial pain patients. The Hybrid model could play an important role in this direction.